Hydroelastic Challenges for Wave-Impact Phenomena in Sloshing Flow - Claudio Lugni; BARDAZZI, ANDREA; Odd M. Faltinsen; GRAZIANI, Giorgio (Volume 9: Odd M. Faltinsen Honoring Symposium on Marine Hydrodynamics, 2013)
Depending on the local flow features before the impact, several and complex scenarios can characterize the physical evolutions of a wave impact in a sloshing flow. As a consequence, flip-through event or wave impact with gas-entrapment may happen causing localized and large loads. In all these cases, when the typical temporal duration of the local load is comparable with the lowest natural period of the structure, hydroelasticity matters affecting the integrity of the structure. Recent paper has shown the importance of the hydroelastic effects during the evolution of a flip-through phenomenon occurring along a deformable plate. Here the experimental investigation is focused on the impact of a wave with air entrapment during shallow-liquid conditions. Several sizes of the cavity entrapped at the wall will be considered by varying the amplitude of the tank motion, measuring the stresses and deformations of the elastic plate.